The fatigue life prediction of gantry crane with load capacity variation using ansys workbench - Lasinta Ari Nendra Wibawa (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2020)
Gantry crane merupakan salah satu jenis crane yang dapat digunakan di dalam dan di luar ruangan. Di kantor LAPAN Garut, gantry crane digunakan untuk proses perakitan roket sebelum dilaksanakan uji statik dan uji terbang. Penelitian ini mengkaji tentang prediksi umur fatik struktur crane menggunakan metode elemen hingga. Desain struktur gantry crane menggunakan Autodesk Inventor Professional 2017, sedangkan analisis elemen hingga menggunakan perangkat lunak Ansys Workbench 2019 R3. Struktur gantry crane dikenakan beban dengan variasi 7, 8, 9, dan 10 ton dengan jenis pembebanan fully-reserved. Prediksi umur fatik menggunakan teori tegangan rata-rata Gerber. Struktur gantry crane menggunakan material aluminium paduan. Hasil simulasi menunjukkan bahwa struktur gantry crane dengan 7, 8, 9, dan 10 ton memiliki umur kelelahan minimum berturut-turut 11,770 x 106, 2,307 x 106, 1,055 x 106, 0,494 x 106 siklus. Sedangkan faktor keamanan struktur gantry crane dengan 7, 8, 9, dan 10 ton memiliki faktor keamanan berturut-turut 1,296; 1,134; 1,008; dan 0.907. Pada pembebanan 10 ton, umur fatik minimum gantry crane kurang dari 1 juta siklus. The gantry crane is one type of crane that can be used indoors and outdoors. In the LAPAN Garut office, the gantry crane is used for the rocket assembly process before static and flight tests are carried out. The study examines the fatigue life prediction of gantry crane structures using the finite element method. gantry crane structure design uses Autodesk Inventor Professional 2017, while finite element analysis uses Ansys Workbench 2019 R3 software. gantry crane structure is subjected to loads with variations of 7, 8, 9, and 10 tons with the fully-reserved type of loading. Fatigue life prediction using Gerber's mean stress theory. gantry crane structure uses aluminium alloy material. The simulation results show that the structure of the gantry crane with 7, 8, 9, and 10 tons have a minimum fatigue life of up to 11.770 x 106, 2.307 x 106, 1.055 x 106, 0.494 x 106 cycles, respectively. While the safety factor of the structure of the gantry crane with 7, 8, 9, and 10 tons have a safety factor of 1.296, 1.134, 1.008, and 0.907, respectively. At a loading of 10 tons, the minimum fatigue life of gantry crane less than 1 million cycles.